The Role of the Village Government in Management of Tourism Objects in Gunung Sari Village, Alok District, Sikka Regency - Irvan, Irvan; Kpalet, Petrus; Natsir, Rodja Abdul (Jurnal Riset Ilmu Pendidikan, 2023)
This study aims to find out how the role of the village government in managing tourism objects in Gunung Sari Village, Alok District, Sikka Regency and what are the obstacles faced by the Gunung Sari Village Government in managing tourism potential. The research method used is a qualitative approach. The data sources in this study are primary data sources and secondary data sources. The selected informants in this study were the secretary of Gunung Sari Village, members of the BPD of Gunung Sari Village, members of Pokdarwis and community leaders of Gunung Sari Village. Data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions. Based on the results of the study that the role of the village government in managing the tourism object of Gunung Sari Village, Alok District, Sikka Regency has carried out its role through activities carried out by the Ministry of Tourism and Culture of Gunu to improve human resources, residents of Gunung Sari Village that it is important to maintain a tourist attraction